PELATIHAN PENGGUNAAN PLATFORM PEMBELAJARAN DI ERA NEW NORMAL BAGI GURU-GURU SD ISLAM INSAN MULIA - Windi Setiawan; Ahmad Hatip (Politeknik Negeri Sriwijaya, 2021)
The COVID-19 pandemic has changed the pattern of our lives every day. We are required to care more about the health of our bodies so that we can avoid the COVID-19 outbreak. The government's efforts to prevent the spread of COVID-19 by asking all citizens to wear masks, diligently wash their hands with soap or handsanitizer and keep their distance. With these regulations, the education system in our country becomes distance learning using the internet. Not all schools can do well, various problems arise when online learning takes place. One of them is SDI Insan Mulia. More than 50% of the teachers at SD Insan Mulia have not been able to use the learning platform to realize effective online learning. Therefore, the abdimas team held training on the use of learning platforms such as google form, edmodo, google classroom, and zoom. The four platforms can be used as media to create interesting learning even though it is done online. This activity is carried out in three stages. In the first stage, the Community Service Team discussed with the principal to determine the implementation of the training. The second stage, the community service team provides training to all teachers at SDI Insan Mulia. The third stage, the Community Service Team evaluates through a questionnaire given when the training is over, followed by assistance to all participants to take advantage of the four platforms. As a result, most of them can make good use of the four platforms.